Investors intention towards supporting crowdfunding for maintenance of school facilities in Melaka - Ismail, Hishamuddin; Bakri, Mohammed Hariri; Abdullah, Muhammad Ridzwan Yap; Kamaruddin, Nur Izaitun; Wee, Stany Liang Fong (Success Culture Press, 2022)
Quality of school facilities and instructional tools are essential to the academic success of both students and teachers while low-standard facilities have an adverse influence on performance in terms of education as well. Malaysian government through the Ministry of Education (MOE) are spending millions to ensure enhancement of quality education in Malaysia especially for the restoration, refurbishment, and formation of new and outdated schools. Lack of maintenance can result in unsafe, unhealthy, and hazardous environment towards students, teachers and supporting staffs that served the public schools. To reduce the economic burden, MOE has launched Maintenance Fund for Government Schools and Public Institutes of Higher Learning which is fully administered by themselves through the crowd-funding concept. Since the concept is still new especially in the context of public education in Malaysia, the attention of this research is to investigate and understanding the factors that might affect potential investors' willingness to contribute to the initiative of crowd-funding. This paper has explained and further justified the extension of UTAUT model which originally used in most of the technology acceptance. The UTAUT has been expanded to also include trustworthiness as new additional variable to complement the original UTAUT. The framework of this study has been developed to improve the understanding of crowdfunding acceptance among the potential investors. To test the framework, data has been collected by using 23 items of structured questionnaire of 5-point Likert scale from 384 potential investors in Melaka. Multiple linear regressions were employed to support the data analysis. The research result indicates that all the independent variables were statistically significant and positive relationships were established. These outcomes suggest that the inclusion of trustworthiness in UTAUT model has increase the prediction level toward potential investors of crowdfunding. Furthermore, it is worth noting that trustworthiness also recorded the highest impact toward the intention to invest among the potential investors. Since the maintenance expenses in government school through crowdfunding is rather new in Malaysia, the findings from this study could assist the government to legalise the crowdfunding which could also be extended to other government services and facilities such as colleges, universities, and the likes. Furthermore, this research can be used as a guide or a reference by industry professionals trying to increase public interest in contributing to a crowd-funding effort. Finally, this study is planned to serve as guideline and policy implication for future government crowd-funding efforts.